2004
DOI: 10.1111/j.1745-493x.2004.tb00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Competitive Environment Influence the Efficacy of Investments in Environmental Management?

Abstract: SUMMARY Supply chain managers confront numerous threats and opportunities in today's competitive environment. Firms simultaneously face increased pressure to lower costs and to be innovative. In addition, most firms are also under increased pressure to improve their environmental (ecological) performance. These rival demands from the competitive environment make it difficult for supply chain managers to determine how a specific investment will influence performance. Thus, inevitable tradeoffs among investments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 26 publications
1
61
1
7
Order By: Relevance
“…Company salary structure is an important component of company motivation mechanism [21]. Forming an incentive system for employees can help to improve employee environmental initiatives, and help enterprises to establish an environment suitable to their needs [22].…”
Section: Sscm Practice and Sustainable Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Company salary structure is an important component of company motivation mechanism [21]. Forming an incentive system for employees can help to improve employee environmental initiatives, and help enterprises to establish an environment suitable to their needs [22].…”
Section: Sscm Practice and Sustainable Performancementioning
confidence: 99%
“…The internal and external SSCM practices are two second-order variables. Internal practices measurement has been measured by a seven-item scale, following Pagell et al [21], Zhu et al [27], and Sila et al [20]. External practices measurement has been measured by a six-item scale measure.…”
Section: Survey Questionnaire and Measuresmentioning
confidence: 99%
“…O investimento das empresas no meio ambiente é considerado uma vantagem competitiva (BERTOLINI et al, 2013;FLORES, 2009;PAGELL et al, 2004). Investimentos em gestão ambiental podem alavancar o desempenho.…”
Section: Sustentabilidade E Empresasunclassified
“…Investimentos em gestão ambiental podem alavancar o desempenho. A criação de produtos e processos limpos requer maneiras novas e inovadoras para produzir (PAGELL et al, 2004).…”
Section: Sustentabilidade E Empresasunclassified
“…Many studies have found that promoting sustainability leads to competitive advantages (e.g. Russo and Fouts 1997;Christmann, 2001;Melnyk et al, 2003;Pagell et al 2004;Rao and Holt, 2005;Montabon et al, 2007;Yang et al, 2010;Huang et al, 2012;Green et al 2012a). …”
Section: Introductionmentioning
confidence: 99%